Carbon/Sulfur Composite Cathodes for Flexible Lithium/Sulfur Batteries: Status and Prospects - Zhao, Yan; Zhang, Yongguang; Bakenova, Zagipa; Bakenov, Zhumabay (Frontiers in Energy Research, 2015)
High specific energy and low cost flexible lithium/sulfur batteries have attracted significant attention as a promising power source to enable future flexible and wearable electronic devices. Here, we review recent progress in the development of free-standing sulfur composite cathodes, with special emphasis on electrode material selectivity and battery structural design. The mini-review is organized based on the dimensionality of different scaffold materials, namely one dimensional carbon nanotube, two dimensional graphene and three dimensional carbon nanotube/graphene composite, respectively. Finally, the opportunities and perspectives of the future research directions are discussed.